EXPLORING THE COMPATIBILITY BETWEEN ENGLISH LANGUAGE TEACHER COMPETENCY FRAMEWORK AND ENGLISH LANGUAGE TEACHER EDUCATION CURRICULUM OF THE UNIVERSITY OF LANGUAGES AND INTERNATIONAL STUDIES – VIETNAM NATIONAL UNIVERSITY, HANOI - Dung, Phung Thi Kim (VNU Journal of Foreign Studies; Vol 34 No 5DO - 10.25073/2525-2445/vnufs.4299, 2018)
Quality assurance is always a key issue in any education system. Among many approaches to enhance national education quality, the practice of designing and implementing competency frameworks for quality language teaching has been adopted in countries across the world. The recent passage of the English Teacher Competency Framework (ETCF) in Vietnam in 2012 reflects the government’s efforts in defining, promoting, and maintaining education quality. This thereby urges language teacher training programs in the country to meet the national teacher standards. But how can the outcomes of a program be formed and mapped to the national system of teacher standards? Is English Language Teacher Education Program (ELTE) introduced in 2012 at the University of Languages and International Studies – Vietnam National University, Hanoi (ULIS – VNU) aligned with the standards in the national ETCF published in December, 2012 by the Ministry of Education and Training? To answer this important question, a study has been conducted to investigate the level of alignment between the ELTE curriculum and the ETCF. By means of document analysis in which course syllabi are examined side by side with the competencies of the framework, the researcher has reached firm conclusions that there are still mismatches and gaps between the curriculum and the ETCF. Several competencies in the ETCF have not been properly addressed in the curriculum while some courses deal with competencies that are not exactly meant in the ETCF. The author then has proposed suggestions for curriculum designers to bring the courses and ETCF standards together to ensure full compatibility between them.